2021
DOI: 10.1007/s40273-020-00993-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma in Portugal: Burden of Disease and Cost of Illness

Abstract: Background Multiple myeloma (MM) is the second most common hematological cancer worldwide and has significant morbidity and mortality and is increasing in incidence. While MM management costs are considerable, specific economic data at the country level remain scarce. Objective This study assesses the burden and cost of MM in Portugal from the perspective of the National Health Service (NHS) to support the definition of health policies, resource allocation and patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
4
17
1
1
Order By: Relevance
“…The greatest costs were attributed to treatment and hospitalisation. This study extends findings of earlier research in Europe that reported lower HCRU costs for MM, but most used smaller cohorts or modelled data [ 14 , 16 , 26 , 27 ]. In one study reporting MM costs for 2018 in Portugal, the average overall annual MM cost burden per patient was lower (€31 K PPPY) than reported here (€58.3 K PPPY) [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The greatest costs were attributed to treatment and hospitalisation. This study extends findings of earlier research in Europe that reported lower HCRU costs for MM, but most used smaller cohorts or modelled data [ 14 , 16 , 26 , 27 ]. In one study reporting MM costs for 2018 in Portugal, the average overall annual MM cost burden per patient was lower (€31 K PPPY) than reported here (€58.3 K PPPY) [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…This study extends findings of earlier research in Europe that reported lower HCRU costs for MM, but most used smaller cohorts or modelled data [ 14 , 16 , 26 , 27 ]. In one study reporting MM costs for 2018 in Portugal, the average overall annual MM cost burden per patient was lower (€31 K PPPY) than reported here (€58.3 K PPPY) [ 27 ]. Yet, the difference in the average annual cost of treatment administration was smaller (€28 K PPPY reported here vs €25 K PPPY reported in Portugal) and both studies show that the cost were mainly driven by the hospitalisations and treatments [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consultations with specialists and hospital visits or admissions explained most direct medical costs during the first year after diagnosis in this study, though the cost of treatments and medications were beyond the study scope. In the burden of illness study conducted by Neves et al 2021 37 in Portugal, pharmacological costs represented more than 60% of the direct medical costs, while hospital admissions that included a 9% transplant related in-hospital stays were the second largest component. The Portuguese authors calculated an average yearly direct costs per patients with MM of €31,449 (year 2018 values) with total direct costs amounting €61 million per year.…”
Section: Discussionmentioning
confidence: 97%
“…Given this intricate disease course and the relatively wide array of therapeutic alternatives, it is increasingly important to understand the real-world economic burden of MM. Although several studies have demonstrated the costs associated with MM in the US and several European countries, far less is known about the economic burden associated with the real-world treatment of MM in Germany [17][18][19][20]. This study aims to bridge this gap by analyzing the healthcare resource utilization and costs in patients with MM, using claims data from a statutory sickness fund in Germany.…”
Section: Introductionmentioning
confidence: 99%